Analysis of the Thermal Elastohydrodynamic Lubrication of Water-lubricated Hybrid Ceramic Bearing - Zhang Tonggang; Wang Youqiang; Xu Caihong; Wang Limei (Jixie chuandong)
The elastohydrodynamic lubrication geometric model of water-lubricated hybrid ceramic journal bearing is established. The numerical simulation of water-lubricated hybrid ceramic bearings considering its thermal effect is carried out by using the Reynolds equation with thermal effect. The effects of supply water pressure on film pressure,film thickness of water-lubricated hybrid ceramics bearing under different working conditions are studied. The region where the local maximum temperature of lubricating film appeared under different working conditions is analyzed. The synergistic effect curve of velocity and load on temperature control of lubricating film of water-lubricated hybrid ceramic bearing is obtained. Results show that the static pressure effect of the initial water supply pressure is favorable to the bearing lubrication,the initial water supply pressure increases,the film thickness of the lubricating film increases,and the pressure change tendency under different working conditions is different. The local maximum temperature of the lubricating film changes under different operating conditions. When the local maximum temperature of the lubricating film is kept at a constant value,the combination of velocity and load has an inverse synergistic effect on the local temperature control of the lubricating film,and the variation trend of the velocity and load is different under different conditions.